Use of Nano-iron Fertiliser Additive Produced by Green Synthesis in Flame Tree (Photinia frasserii) and Smoke Tree (Cotinus coggyria) Cultivation - Babali, Neslihan; Nadaroglu, Hayrunnisa; Demir, Taki; Alayli, Azize (Indonesian Journal of Social and Environmental Issues (IJSEI), 2024)
This research aims to develop a novel nano-fertilizer additive through the use of nano-technological principles. The synthesis of iron nanoparticles was carried out using water-soluble iron salt and pomegranate plant extract as a green synthesis reaction medium, thus creating an innovative and environmentally friendly approach. A comprehensive analysis of the synthesized particles was carried out using various advanced techniques such as SEM, TEM, XRD, FT-IR, and UV-Vis, elucidating their complex morphological and elemental properties and confirming their nanoscale size. Then, the application of the produced nano-fertilizer on specific plant species (Smoke and Flame Tree) was investigated to evaluate its effect on plant growth. In this context, the nano-fertilizer was applied to plant tissue cultures grown under controlled and sterile conditions in the plant tissue laboratory, followed by a comparative analysis with control groups. The results of the study revealed the superior efficacy of nano-iron based nano-fertilizer, which requires significantly less amount of iron compared to conventional iron fertilizers. Multiple parameters were considered for the analysis of the results. In particular, the application of nano fertilizer gave more favorable results for the growth of the Flame tree (Photinia fraserii) when the nanodimer was used at a ratio of 1/46 to the standard iron-containing medium. Similarly, for the Smoke tree (Cotinus coggygria), favorable effects on plant growth were observed at a ratio of 1/34 compared to the standard iron-containing medium. These findings suggest that nano-fertilizer formulations containing synthesized nano-iron additives can increase agricultural yield, minimize environmental impact, and contribute positively to overall plant production.